Circulating Tumour DNA: A Blood Test for Monitoring Cancer - Mansour, Mark (The Meducator, 2016)
DNA fragments found in blood plasma, known as circulating tumour DNA (ctDNA), act novel biomarkers for cancer diagnosis. Through a simple blood draw, ctDNA allows for the genetic characterization of a patient’s cancer, which in turn can guide clinical decisions when prescribing a narrow spectrum chemotherapy drug. Current methods in cancer genotyping involve invasive biopsy resections which often compromise patient quality of life, are subject to issues regarding cell heterogeneity, make it difficult to detect secondary tumours, and often provide insufficient yields for genetic sequencing. Meanwhile, ctDNA allows clinicians and researchers alike to monitor the progression of a patient’s condition by prospectively collecting multiple blood samples. While not considered common clinical practice, ctDNA analysis has been successfully used to diagnose breast, gastric, colorectal, utero-ovarian, and lung cancers while clinical trials are currently being done for various others. Through ctDNA sequencing, clinicians are capable of characterizing a tumour in a non- invasive manner, consequently allowing them to deliver patient-specific cancer care.